Social entrepreneurship: The need, relevance, facets and constraints - Tanvi Gandhi; Rishav Raina (Journal of Global Entrepreneurship Research, 2018)
Social entrepreneurship is gradually becoming a crucial element in the worldwide discussion on volunteerism and civic commitment. It interleaves the passion of a common cause with industrial ethics and is notable and different from the present other types of entrepreneurship models due to its quest for mission associated influence. The previous few years have noticed a striking and surprising progress in the field of social entrepreneurship and has amplified attention ranging throughout all the diverse sectors. The critical difference between social and traditional entrepreneurship can be seen in the founding mission of the venture and the market impressions. Social entrepreneurs emphasize on ways to relieve or eradicate societal pressures and produce progressive externalities or public properties. This study focuses mainly on the meaning of social entrepreneurship to different genres and where does it stand in respect to other forms of entrepreneurship in today's times.
Keywords: 650; Social entrepreneurship (SE); Entrepreneur; Society; Non-profit ventures; Corporate social responsibility (CSR)